Soft Soil Consolidation with the Electroosmosis Effect - Hurun 'Ain; Firmanilah Kamil (Applied Research on Civil Engineering and Environment (ARCEE), 2022)
Areas with geomorphology in plains or lowlands, such as Pontianak City, have soft soil and peat covering most of their area. Lands in areas with low soil bearing capacity, high water content, high compressibility properties, and high groundwater levels or even practically the same as the land surface. Theoretically, soil improvement is preferred over several other options such as relocation, redesign, and replacement of unsuitable soils. Electroosmosis is one of the effective methods to reduce the moisture content in soft clay to reduce the amount of settlement that occurs when loading is carried out. The use of electroosmosis by placing a conductor in the ground with a certain distance, then between the conductors, an electric current is given. By reducing the water content in the soil, the decrease in soil subsidence will decrease and increase the strength of the soil. This electroosmosis test was carried out in a laboratory with a test model using a PVC pipe tube with a length of 19 cm and a diameter of 15 cm using five conductor rods. The soil specimens are subjected to two cases: direct loading and preloading during the electroosmosis test. Tests were conducted to study the effect of the current magnitude applied with a particular voltage on the physical and mechanical properties of the soil. The tests showed a significant of settlement with 0.0679 cm and 0.0663 cm for direct loading and preloading with the current effect. The mechanical properties showed an improvement in the soil samples, which was indicated by a low compressibility index and an increase in the shear strength of the soil.